Mechanisms underlying targeted mitochondrial therapy for programmed cardiac cell death - Jing, Fengting; Zhao, Min; Xiong, Hemin; Zeng, Xin; Jiang, Jun; Li, Tao (Frontiers in Physiology, 2025)
Heart diseases are common clinical diseases, such as cardiac fibrosis, heart failure, hypertension and arrhythmia. Globally, the incidence rate and mortality of heart diseases are increasing by years. The main mechanism of heart disease is related to the cellular state. Mitochondrion is the organ of cellular energy supply, participating in various signal transduction pathways and playing a vital role in the occurrence and development of heart disease. This review summarizes the cell death patterns and molecular mechanisms associated with heart disease and mitochondrial dysfunction.